2018
DOI: 10.1177/0734242x18778773
|View full text |Cite
|
Sign up to set email alerts
|

Fast prediction of organic wastes methane potential by near infrared reflectance spectroscopy: A successful tool for farm-scale biogas plant monitoring

Abstract: Currently, there is a growing worldwide interest for the treatment of wastes, and especially farm wastes, by anaerobic digestion. Biochemical methane potential is a key parameter for the design, optimisation and monitoring of the anaerobic digestion process, but it is also time consuming (4-7 weeks). Near infrared reflectance spectroscopy seems a promising method to predict the biochemical methane potential of a wide range of organic substrates. This study compares a 'global' predictive model mainly built with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Methane yields obtained in the present study are similar to the yields of 129 to 366 NL CH 4 kg −1 VS reported in the literature for cow manure [ 25 , 29 , 35 ]. The composition of cow manure is dependent on the animal species, the bedding material used and the feed composition.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Methane yields obtained in the present study are similar to the yields of 129 to 366 NL CH 4 kg −1 VS reported in the literature for cow manure [ 25 , 29 , 35 ]. The composition of cow manure is dependent on the animal species, the bedding material used and the feed composition.…”
Section: Resultssupporting
confidence: 89%
“…Nonetheless, two publications found similar mean for large set of manure sample. Mortreuil et al (2017) measured the methane performance of 58 solid manures with an ISR of 2.8 and found a mean of 225 NL CH 4 /kg VS (range of 129–366 NL CH 4 /kg VS) [ 35 ]. Similarly, Rodrigues et al (2018) performed BMP tests on 12 manures (ISR at 2) and obtained a mean of 211 NL CH 4 /kg VS (from 154 to 325 NL CH 4 /kg VS) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the conversion processes, all three biofuels can be produced via a biochemical or the thermochemical pathway [56][57][58]. Both feedstock and production process influence the economic sustainability, showing that crop-based biofuels have a high feedstock cost and low capital cost, compared to the relatively low cost for feedstock and high capital cost for the biofuels from lignocellulosic biomass, wastes, and residues [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]. Moreover, the latter are also significantly more environmental and socioecological sustainable compared to the crop feedstock that imposes the impacts of land use and land-use change.…”
mentioning
confidence: 99%